2019
DOI: 10.1155/2019/7087232
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Pepsinogen in GC Screening: A Systematic Review and Meta-Analysis

Abstract: Background The current gold standard for gastric cancer (GC) screening is pathology or a barium meal followed by X-ray. This is not applicable to a wide range of screening capabilities due to the lack of operability. This article used a meta-analysis to evaluate the value of pepsinogen (PG) screening for GC. Methods PubMed, EMbase, the Cochrane Library, CNKI, WanFang, VIP, and CBM databases were systematically searched for published studies that used serum PG to diagnose GC. Articles were searched from January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
0
14
1
Order By: Relevance
“…Compared to the previous meta-analyses that combined the diagnostic values with various cut-off standards in a single outcome, the results of this study showed slightly lower diagnostic values (AUC for the diagnosis of CAG: 0.81 vs. 0.85/AUC for the diagnosis of GC: 0.70 vs. 0.76/DOR for the diagnosis of GC: 4 vs. 5.41), indicating overestimation of diagnostic validity in previous studies [9,10].…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Compared to the previous meta-analyses that combined the diagnostic values with various cut-off standards in a single outcome, the results of this study showed slightly lower diagnostic values (AUC for the diagnosis of CAG: 0.81 vs. 0.85/AUC for the diagnosis of GC: 0.70 vs. 0.76/DOR for the diagnosis of GC: 4 vs. 5.41), indicating overestimation of diagnostic validity in previous studies [9,10].…”
Section: Discussioncontrasting
confidence: 46%
“…Although various cut-off values have been suggested, the combination of PG I ≤70 ng/mL and PG I/PG II ratio ≤3 have been proposed for the prediction of CAG or GC [4,8]. However, previous meta-analyses for diagnostic test accuracy (DTA) presented only pooled outcomes, which cannot determine the diagnostic validity of sPGA with a cut-off value of PG I ≤70 ng/mL and PG I/PG II ratio ≤3 [9,10], although no threshold effect was detected [9]. This can lead to an exaggerated summary of performance because pooled analysis adopted the best performance value in each study, irrespective of cut-off values.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that a low serum PGI level and low PGI/PGII ratio have been associated with severe gastric atrophy, intestinal metaplasia, and are frequently found in gastric cancer. [ 4 , 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…13 However, the sensitivity of this approach as reported in metaanalyses ranges from 56% to 69%, though the specificity is 71% to 73%. 14,15 Even these numbers may be an overestimation, since several studies have demonstrated that normal pepsinogen levels are found in approximately two-thirds of patients who have gastric cancer. 11 The current study has demonstrated significantly better results for detecting gastric cancer when compared with pepsinogen measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the best available noninvasive screening tools for atrophy, the precancerous lesion for gastric cancer, is detection of pepsinogen I and II levels in the circulation 13 . However, the sensitivity of this approach as reported in meta‐analyses ranges from 56% to 69%, though the specificity is 71% to 73% 14,15 . Even these numbers may be an overestimation, since several studies have demonstrated that normal pepsinogen levels are found in approximately two‐thirds of patients who have gastric cancer 11 .…”
Section: Introductionmentioning
confidence: 99%